Phanerozoic biodiversity, macrotaxa and families - Johannes Pignatt, Longino Contoli (Journal of Mediterranean Earth Sciences, 2014)
Traditionally, global Phanerozoic diversity patterns of eukaryotes have been studied by analyzing the variation of the number of taxa at family or genus rank in time. The question of which global processes these diversity patterns reflect remains unanswered. We show that for understanding Phanerozoic biodiversity an ecological-taxonomic approach is preferable to a purely taxonomic approach. Consequently, an ecologically modified taxonomic unit, the macrotaxon, is introduced. This approach allows us to exploit the potential of complex diversity indices, as well as the richness and evenness components.